Environmental, Social, and Governance Performance and Stock Investment Risk: The Distinct Role of the Environmental Dimension - Gilberth Haris Aditya Parhusip; Wendy; Anwar Azazi; M. Ridwan Ristyawan; Uray Ndaru Mustika (Al-Qalam Institue, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) performance on stock investment risk and to investigate the moderating role of market capitalization in the relationship between ESG performance and stock investment risk. Panel data regression analysis was employed using the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Model selection was conducted through the Chow, Hausman, and Lagrange Multiplier tests, with the Random Effect Model identified as the most appropriate estimation model. The findings reveal that overall ESG performance has no significant effect on stock investment risk. Likewise, the interaction between ESG performance and market capitalization does not significantly moderate the relationship. Further analysis of ESG dimensions shows that the Environmental dimension has a negative and statistically significant effect on stock investment risk at the 10% significance level, while the Social and Governance dimensions do not exhibit significant effects. These findings imply that aggregate ESG performance has not yet become a strong determinant of stock investment risk, although environmental performance may contribute to reducing investment risk. The results provide insights for investors and corporate managers regarding the importance of strengthening environmental practices as part of long-term risk management strategies.